AIGenducation: Dampak dan Strategi Menghadapi Revolusi Industri 5.0 pada Siswa Berbasis Value Expectancy Theory - Julius, Keishya Shalisa; Putri, Nadhira Halizah; Ibadi, Angela Ahmad; Wynnemaida, Vania; Kirana, Harnum Widya Candra; Indrijati, Herdina (Buletin Riset Psikologi dan Kesehatan Mental, 2024)
Artificial intelligence can improve human efficiency and productivity, especially in the industrial revolution 5.0. However, the use of AI in education has risks such as overuse of AI that leads to dependence, laziness in learning, and increased plagiarism. This study used a mixed method with a parallel convergent design. Pearson correlation analysis was conducted to determine the correlation between knowledge about AI and motivation to learn and internet plagiarism, as well as the correlation between knowledge, perceived value, and perceived cost on intention to use AI. The relationship between knowledge of AI as the independent variable and motivation to learn and internet plagiarism as the dependent variable was examined as well as the mediating role of intention to use AI through GLM Mediation Models. The quantitative research accepted four and rejected three hypotheses. The qualitative research revealed the factors, impacts, and strategies of using Generative AI in educational settings.